2021
DOI: 10.1016/j.hrcr.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular fibrillation in Graves disease reveals a rare SCN5A mutation with W1191X variant associated with Brugada syndrome

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…An ECG that was performed after she was re-admitted for fever and pleural effusion exhibited the type 2 BrS ECG pattern, although the report is unclear whether she performed ECG at the time of the actual fever. Genetic testing revealed a likely pathogenic mutation in the SCN5A gene (130). Therefore, genetic studies could be helpful to better understand the link between the manifestation of the BrS ECG pattern and thyroid dysfunction.…”
Section: Brugada Syndrome and Thyroid Dysfunctionmentioning
confidence: 99%
“…An ECG that was performed after she was re-admitted for fever and pleural effusion exhibited the type 2 BrS ECG pattern, although the report is unclear whether she performed ECG at the time of the actual fever. Genetic testing revealed a likely pathogenic mutation in the SCN5A gene (130). Therefore, genetic studies could be helpful to better understand the link between the manifestation of the BrS ECG pattern and thyroid dysfunction.…”
Section: Brugada Syndrome and Thyroid Dysfunctionmentioning
confidence: 99%
“…Although these patients typically do not show ventricular tachycardia or TdP, hypothyroidism exacerbates the arrhythmogenic risk in BrS, especially in those with SCN5A mutations. These mutations, coupled with thyroid conditions such as thyrotoxicosis ( 18 ) or hypothyroidism ( 19 ), increase the likelihood of ventricular arrhythmias in this high-risk group. Thus, thyroid states can crucially influence SCN5A function, heightening the arrhythmogenic potential in BrS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a genetic predisposition for arrhythmias, thyrotoxicosis can lower the arrhythmia threshold, and in rare cases, ventricular fibrillation may occur. A recent case report described a patient carrying the SCN5A mutation who developed ventricular fibrillation in the setting of hyperthyroidism [25]. SCN5A mutations have been implicated in the pathogenesis of long QT syndrome, BrS, and cardiomyopathy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nav1.5, the pore forming α-subunit of the voltage-dependent cardiac Na+ channel, is not exclusively expressed in heart but has also been detected in the brain and gastrointestinal smooth muscle [27]. It has been reported that SCN5A-mediated abnormal cardiac phenotypes overlap with epilepsy [28][29][30], hyperthyroidism [25], and irritable bowel syndrome. Thus, some researchers propose concepts of overlap syndromes and systemic disorders in relation to SCN5A-mediated cardiac disfunctions [31].…”
Section: Discussionmentioning
confidence: 99%